Functional echocardiography training in the neonatal intensive care unit: comparing measurements and results with the pediatric cardiologist - Marina Maccagnano Zamith; Simone de Araujo Negreiros Figueira; Allan Chiaratti de Oliveira; Cristiane Metolina; Junia Sampel de Castro; Cristina Nunes dos Santos; Ana Leticia de Oliveira Abrahão de Capo; Valdir Ambrósio Moisés (Elsevier, 2020)
Objectives: Functional echocardiography is a valuable tool in the neonatal intensive care unit, but training programs are not standardized. The aim was to report an functional echocardiography training program for neonatologists and to describe the agreement of their measurements with the pediatric cardiologist. Methods: Functional echocardiography training lasted 32 h. After training program, the neonatologists performed functional echocardiography in the neonatal intensive care unit and were required to measure left cardiac chambers dimensions, left ventricle systolic function, right and left ventricular output, ductus arteriosus diameter, and flow pattern. Images were recorded by the equipment and reviewed offline by the pediatric cardiologist. The Bland-Altman test was used for quantitative variables and the kappa test, for qualitative variables. Results: Twenty-two trained neonatologists performed 100 functional echocardiography exams. Ductus arteriosus identification and flow pattern had substantial agreement (kappa = 0.91 and 0.88, respectively), as well as its diameter (mean difference = 0.04 mm). The mean difference for the aortic root was −1.2 mm; left atrium, 0.60 mm; left ventricle diastolic diameter, −0.90 mm; left ventricle systolic diameter, −0.30 mm. Shortening fraction and ejection fraction correlated well with broad limits of agreement, −2.96% (14.88; −20.82%) and −-3.43% (15.54; −22.40%), respectively. Right and left ventricular output had broad limits of agreement, 16.69 mL/kg/min (222.76; −189.37) and 23.57 mL/kg/min (157.88; −110), respectively. There was good agreement between interpretations of normal or low cardiac output (76.7% for right ventricular output; 75.7% for left ventricular output). Conclusion: This functional echocardiography training program enabled neonatologists to obtain adequate skills in performing the images, obtaining good agreement with the cardiologist in simple hemodynamic measurements and ductus arteriosus evaluation. Resumo: Objetivos: A ecocardiografia funcional é uma ferramenta valiosa na unidade de terapia intensiva neonatal, mas os programas de treinamento não são padronizados. Nosso objetivo foi relatar um programa de treinamento em ecocardiografia funcional para neonatologistas e descrever a concordância de suas medidas com o cardiologista pediátrico. Métodos: O treinamento em ecocardiografia funcional durou 32 horas. Após o programa de treinamento, os neonatologistas faziam ecocardiografia funcional na unidade de terapia intensiva neonatal e mediam as dimensões das câmaras cardíacas esquerdas, função sistólica do ventrículo esquerdo, débito cardíaco do ventrículo direito e débito cardíaco do ventrículo esquerdo, diâmetro do canal arterial e o padrão de fluxo. As imagens foram registradas no equipamento e revisadas offline pelo cardiologista pediátrico. O teste de Bland-Altman foi usado para variáveis quantitativas e o teste Kappa para variáveis qualitativas. Resultados: Foram feitas por 22 neonatologistas treinados 100 ecocardiografias funcionais. A identificação do canal arterial e o padrão de fluxo apresentaram concordância substancial (Kappa = 0,91 e 0,88, respectivamente), bem como seu diâmetro (diferença média = 0,04 mm). A diferença média foi de -1,2 mm para a raiz da aorta, 0,60 mm para o átrio esquerdo, -0,90 mm para o diâmetro diastólico do ventrículo esquerdo e de -0,30 mm para o diâmetro sistólico do ventrículo esquerdo. A fração de encurtamento e a fração de ejeção apresentaram boas correlações, com amplos limites de concordância, respectivamente -2,96% (14,88; -20,82%) e -3,43% (15,54; -22,40%). Os débitos cardíacos do ventrículo direito e do ventrículo esquerdo apresentaram amplos limites de concordância, 16,69 mL/kg/min (222,76; -189,37) e 23,57 mL/kg/min (157,88; -110), respectivamente. Houve boa concordância entre a interpretação de débito cardíaco normal ou baixo (76,7% de débito ventricular direito; 75,7% de débito ventricular esquerdo). Conclusão: Esse programa de treinamento em ecocardiografia funcional permitiu aos neonatologistas obter habilidades adequadas na realização das imagens, com boa concordância com o cardiologista em medidas hemodinâmicas simples e avaliação do canal arterial.